Analisis Struktur Tubuh Aurelia aurita Sebagai Hewan Diploblastik Berdasarkan Lapisan Embrional dan Karakteristik Morfologi dalam Filum Cnidaria - Alia Petra Siboro; M. Farhan Aditiya; Julian Pratama; Jodion Siburian; Afreni Hamidah; Desfaur Natalia (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to analyze the body structure of Aurelia aurita as a diploblastic organism based on its embryonic layers and morphological characteristics within the phylum Cnidaria. The research employed a literature study method using a qualitative descriptive approach through the review of journals, books, and scientific articles published between 2022 and 2026. Data collection was conducted by identifying, selecting, and examining relevant scientific sources related to the anatomy, morphology, and developmental biology of Aurelia aurita. The collected data were analyzed systematically through reduction, classification, interpretation, and presentation stages to obtain comprehensive findings. The results showed that Aurelia aurita possesses two main embryonic layers, namely ectoderm and endoderm, with mesoglea acting as a supporting layer between them. The ectoderm develops into the epidermis, tentacles, and cnidocytes functioning in defense and prey capture, while the endoderm develops into the gastrodermis and gastrovascular cavity responsible for digestion and nutrient distribution. Morphologically, this organism has a transparent umbrella-shaped body, radial symmetry, oral arms, a diffuse nervous system, and simple organ systems functioning through diffusion mechanisms. These body structures support the adaptability, survival, feeding efficiency, and ecological role of Aurelia aurita in aquatic environments effectively.